Feasibility study of an incremental field test based on GNSS-RTK power feedback - Bortolan, L.; Savoldelli, A.; Decet, M.; Pellegrini, B. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Ski-mountaineering is one of the most demanding endurance sports. Researchers have extensively proven the relevance of VO2max, VO2@VT2, and GE on race performance. Different laboratory tests have been developed to measure the above-mentioned parameters on ski mountaineering athletes, while adequate methods for field evaluation are still lacking. Here, we tested the feasibility of performing an incremental test by using a GNSS-RTK to provide feedback to the athletes related to their punctual vertical speed.